The Antibacterial Activity of Ethanol Extract, n-Hexane Fraction, and Ethyl Acetate Fraction of Water Hyacinth Leaves (Eichhornia crassipes) Growing on the Banks of the Mahakam River Against Propionibacterium acnes: Aktivitas Antibakteri Ekstrak Etanol, Fraksi n-Heksana dan Fraksi Etil Asetat Daun Eceng Gondok (Eichhornia crassipes) yang Tumbuh di Tepi Sungai Mahakam Terhadap Propionibacterium acnes - dewi, herlina ekapratama; Cahya, Muhammad Dwi Cahya; Pratiwi, Putri Rinda (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Propionibacterium acnes is a gram-positive bacterium that causes acne. Water hyacinth (Eichhornia crassipes) is a plant commonly found along the banks of the Mahakam River that has antibacterial properties. The purpose of this study was to perform a phytochemical screening and determine the antibacterial activity of the ethanol extract, n-hexane fraction, and ethyl acetate fraction of water hyacinth (Eichhornia crassipes) leaves against Propionibacterium acnes bacteria. Antibacterial activity was measured by the diameter of the inhibition zone using the agar diffusion method. Phytochemical screening results showed that the ethanol extract and ethyl acetate fraction of water hyacinth leaves were positive for flavonoids, alkaloids, and tannins, while these metabolites were not found in the n-hexane fraction. Each test solution was prepared at concentrations of 5%, 7.5%, 15%, and 30%. The antibacterial activity test yielded average inhibition zone diameters for the ethanol extract, n-hexane fraction, and ethyl acetate fraction of 12.70 mm, 12.85 mm, and 13.17 mm, respectively.